2016
DOI: 10.1097/mpg.0000000000001034
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Infliximab Is Associated With Disease Extent in Children With Inflammatory Bowel Disease

Abstract: Patients with extensive disease started taking 5 mg/kg of IFX were more likely to require dose escalation compared to those with limited or moderate disease. All of the patients with moderate and extensive disease started taking 10 mg/kg of IFX remained on this dose. These results suggest that patients with more extensive disease may benefit from higher initial IFX dosing as it relates to durability of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
0
17
2
Order By: Relevance
“…To the best of our knowledge, this is the first study to address differences in the therapeutic effects in CD according to NUDT15 activity. The factors associated with LOR are colonic involvement, young age at IFX initiation, smoking, concomitant immunomodulators, IFX TLs and development of ATIs 23,24 . In this study, no significant differences were found in variables reported to affect LOR, as well as in treatment outcomes such as CR, BR and MH at 1 year according to NUDT15 phenotype.…”
Section: Discussioncontrasting
confidence: 54%
“…To the best of our knowledge, this is the first study to address differences in the therapeutic effects in CD according to NUDT15 activity. The factors associated with LOR are colonic involvement, young age at IFX initiation, smoking, concomitant immunomodulators, IFX TLs and development of ATIs 23,24 . In this study, no significant differences were found in variables reported to affect LOR, as well as in treatment outcomes such as CR, BR and MH at 1 year according to NUDT15 phenotype.…”
Section: Discussioncontrasting
confidence: 54%
“…Recent reports have described potential benefits of accelerated infliximab induction regimens for optimal disease control and reducing the early colectomy rate in severe UC ( 24 , 25 ). Shapiro et al suggest that an initial intensive regimen is necessary in extensive disease (90% of the patients in this study) to maintain sustained efficacy ( 26 ). Therapeutic drug monitoring may be a useful adjunct to clinical judgment to identify which patients need therapy escalation with infliximab ( 27 ).…”
Section: Discussionmentioning
confidence: 86%
“…1 The incidence of IBD is rapidly increasing worldwide and approximately 25% of IBD patients are diagnosed in early ages. 1,2 I Extra-intestinal manifestations including oral cavity are more commonly seen at the disease onset in pediatric IBD patients than adults. 3 The prevalence of oral manifestations of IBD ranges widely from 7% to 23% in children (up to 41% in children with CD).…”
Section: Introductionmentioning
confidence: 99%
“…5 The main mechanisms of IBD pathogenesis are dysregulated host immune response to commensal microbiota and disruption of pro-and antiinflammatory cytokines' balance in genetically predisposed individuals. 1,2,6 Although UC is limited to the superficial mucosa of the colon, CD progresses with transmural inflammation in any part of the gastrointestinal system from mouth to anus. 1 Although the main focus of studies have been oral mucosal lesions rather than periodontal disease, there are some studies demonstrating the increased risk of periodontitis in patients with IBD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation